2016
DOI: 10.1159/000443458
|View full text |Cite
|
Sign up to set email alerts
|

Serum Anti-Müllerian Hormone Concentration in Young Women with Chronic Kidney Disease on Hemodialysis, and After Successful Kidney Transplantation

Abstract: Background/Aims: In women with chronic kidney disease (CKD) fertility abnormalities occur frequently. Anti-Müllerian hormone (AMH) inhibits excessive recruitment of primordial follicles. The aim of the study was to evaluate the serum AMH concentration in women on hemodialysis and after kidney transplantation (KTx). Methods: 46 hemodialysed women and 14 with CKD about to undergo kidney transplantation were enrolled into the study. The control group consisted of 40 healthy women. In all subjects serum concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 31 publications
1
34
2
Order By: Relevance
“…Results of this study go in agreement with those that have been found with (15), who showed that CKD patients were found to have nonsignificant increase in AMH concentrations compared with control. The results of this study were compatible with data reported by (14), who found that serum AMH concentration was higher in haemodialysed women with CKD and had menstrual cycle abnormalities in comparison to those with regular menstrual cycles, and suggested that serum AMH clearance is reduced in CKD patients and AMH similar to other protein hormones probably accumulates in those patients (16). On the other hand, AMH is of similar size to other molecules perceived to be uremic 'toxins' (17).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results of this study go in agreement with those that have been found with (15), who showed that CKD patients were found to have nonsignificant increase in AMH concentrations compared with control. The results of this study were compatible with data reported by (14), who found that serum AMH concentration was higher in haemodialysed women with CKD and had menstrual cycle abnormalities in comparison to those with regular menstrual cycles, and suggested that serum AMH clearance is reduced in CKD patients and AMH similar to other protein hormones probably accumulates in those patients (16). On the other hand, AMH is of similar size to other molecules perceived to be uremic 'toxins' (17).…”
Section: Discussionsupporting
confidence: 91%
“…CKD and its consequences affect the production of AMH, resulting in change in plasma AMH levels, this may indicate impaired function of Sertoli cells (13). In women with CKD the aforementioned fertility disturbances may be caused by the damage of the ovaries by uremia, this may reflect an intrinsic dysregulation of the granulosa cells leading to higher AMH production or alternatively AMH accumulation in ESRD requiring dialysis (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, fertility is frequently restored within a few months after successful kidney transplantation (Levidiotis et al, 2009). To date we are only aware of a single small study (n = 60) assessing AMH in patients with renal failure (Sikora-Grabka et al, 2016). This study utilized a manual AMH ELISA, which was limited by complement interference, irreproducible results and limited sensitivity (Iliodromiti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In dialysis patients, an elevation of FSH concentrations also indicates true menopause [14]. Serum AMH concentrations were found to be similar in dialysis patients and healthy controls [16,17] and thus we used low AMH concentrations to ascertain infertility in selected cases. We also described LH serum concentrations, which are usually elevated in case of menopausal transition, infertility or in dialysis patients [18,19].…”
Section: Methodsmentioning
confidence: 99%